Determination of Flavonoid Content of Ethanol Extract of Yellow Pumpkin Leaves (Cucurbita moschata Dulchesne ) Using Uv-Vis Spectrophotometry - Dewi Gulyla Hari; Tri Nova Lovena; Ummul Khairiah (Jurnal FARMASIMED (JFM), 2025)
Background: Flavonoids are one of the most abundant groups of secondary metabolite compounds found in plant tissues. Pumpkin leaves (Cucurbita moschata Dulchesne ) can generally be used as antidiabetic, analgesic, nephroprotective and anticancer for stomach pain, jaundice, skin infections, lowering cholesterol, and blood sugar levels, and contain flavonoid compounds. Purpose: to determine the levels of flavonoid compounds contained in 70% ethanol extract of pumpkin leaves (Cucurbita moschata Dulchesne ). Methods: using the UV-Vis spectrophotometry method and to determine the flavonoid content from the results of phytochemical screening in the ethanol extract of pumpkin leaves. Pumpkin leaf extract was obtained through maceration techniques with 70% ethanol as the solvent. Results: The study showed that there was flavonoid content in pumpkin leaves, which was orange in color and the results of the study determined the flavonoid levels using UV-Vis spectrophotometry at a wavelength of 428 nm. om the resultsobtained from the measurement of the standard curve of quarcetin, it can be concluded that the higher the concentration used, the higher the absorbance value obtained and it can be seen that the results obtained total flavonoid content in the 70% ethanol extract sample of pumpkin leaves is 7.2672 mgQE/g.  Conclusion: There is a flavonoid compound content contained in pumpkin leaves.